2021
DOI: 10.3389/fgene.2021.745508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of the MGISEQ-2000 and Illumina X-Ten Sequencing Platforms for Paleogenomics

Abstract: The MGISEQ-2000 sequencer is widely used in various omics studies, but the performance of this platform for paleogenomics has not been evaluated. We here compare the performance of MGISEQ-2000 with the Illumina X-Ten on ancient human DNA using four samples from 1750BCE to 60CE. We found there were only slight differences between the two platforms in most parameters (duplication rate, sequencing bias, θ, δS, and λ). MGISEQ-2000 performed well on endogenous rate and library complexity although X-Ten had a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Despite the importance of this assay, no investigation has been conducted to compare the performance of the highly economical BGI sequencing technology relative to the generally employed Illumina technology for this critical library type. Here we complement published knowledge about BGI sequencing technology by showing that it cannot only generate data for RNA-seq (Senabouth et al, 2020;Natarajan et al, 2019) and whole-genome DNA libraries (Mak et al, 2017;Zhu et al, 2021) but also for ATAC-seq libraries at levels comparable to an Illumina platform. More specifically BGI's DNBSEQ-G400 instrument enabled the generation of chromatin accessibility data that could be used to identify master TFs that underpin cell identity, with motif enrichment, TF aggregate and de novo foot-printing capabilities equivalent to data from an Illumina platform.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite the importance of this assay, no investigation has been conducted to compare the performance of the highly economical BGI sequencing technology relative to the generally employed Illumina technology for this critical library type. Here we complement published knowledge about BGI sequencing technology by showing that it cannot only generate data for RNA-seq (Senabouth et al, 2020;Natarajan et al, 2019) and whole-genome DNA libraries (Mak et al, 2017;Zhu et al, 2021) but also for ATAC-seq libraries at levels comparable to an Illumina platform. More specifically BGI's DNBSEQ-G400 instrument enabled the generation of chromatin accessibility data that could be used to identify master TFs that underpin cell identity, with motif enrichment, TF aggregate and de novo foot-printing capabilities equivalent to data from an Illumina platform.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, approximate costs for generating 600–800 million reads (=300–400 million read pairs) at 150 bp via Illumina’s HiSeqX10 are $1600 USD. While BGI platforms have been evaluated to be comparative in performance to Illumina platforms for sequencing of RNA-seq libraries ( Fehlmann et al, 2016 ; Zhu et al, 2018 ; Natarajan et al, 2019 ; Senabouth et al, 2020 ) and whole-genome DNA libraries ( Mak et al, 2017 ; Kim et al, 2021 ; Zhu et al, 2021 ), to date no study has compared Illumina and BGI platforms for their ability to sequence ATAC-seq libraries and recover the accessible cellular chromatin landscape.…”
Section: Introductionmentioning
confidence: 99%
“…For our 34 samples, we extracted DNA from the temporal bones, teeth and limb bones (Table 1 and Supplementary Table 1A), using a dedicated aDNA facility in Fudan University, Shanghai. Molecular methods used for aDNA extraction and construction of Illumina libraries have been described previously (Zhu et al, 2021;Xiong et al, 2022). One extraction (no sample powder used) and one PCR blank (extract supplemented by water) were set up as negative controls for each batch of samples.…”
Section: Dna Extraction and Library Preparationmentioning
confidence: 99%
“…Frequency of index misassignment of the DNBSEQ platform, which used a combinatorial Probe-Anchor Synthesis method and DNA nanoball sequencing technology developed by MGI, was demonstrated to be as low as 0.0001-0.0004% [28]. Studies evaluating these different sequencing platforms in whole genome sequencing have been conducted by researchers worldwide [29,30]. In metagenomic studies, index misassignment has also been demonstrated to be an overlooked source of error in metabarcoding amplicon studies using pyrosequencing [22] or Illumina sequencing technology [31,32] for a decade.…”
Section: Introductionmentioning
confidence: 99%